Clinic Management System - Tee, Ee Kee; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2023)
Clinic Management System is a web-based system that facilitates the management of business-related information at Teck Hoe Clinic. At the moment, the clinic's proprietor has to manually record all of the clinic's information. As a result, data redundancy, data inconsistency, data loss, and even time waste are all encountered. Consequently, the aim of this project is to develop, design, and test the management system for the clinic. To develop the system, Hypertext Markup Language (HTML) and Cascading Style Sheets (CSS) are used as front-end languages. Furthermore, Hypertext Preprocessor (PHP) is used as the main back-end language. Microsoft Azure is used as the web server for hosting the system and Filess.io is used as database hosting. A waterfall model was chosen with five phases including planning, analysis, design, implementation, and testing. With the system, clinic data will be managed effectively that cannot be handled via manual recording methods. The workload in managing the clinic's data can be reduced. Finally, it assists the clinic in managing and organizing data to ensure smooth business operations.